Beliefs, Practices, and National Ideologies as Triggers for Change in Language Policy and Planning and in Future Aspirations: The Case of Algeria - Maraf, Baya (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The present thesis discusses language policy of foreign languages (mainly English) in a multilingual context, Algeria. The study responds to the call of Spolsky (2004) to test his theory of language policy in independent nations. In addition to the beliefs, practices and management of language were considered in testing the theory. The research aims to answer five research questions: 1) What are the beliefs and national ideology of Algerians on foreign languages that triggered the change symptoms in foreign language policy in Algeria? 2) How are the Algerians' practices in English language different after the Smile Revolution? 3) How do the participants view the impact of English language practices on post-SR government decisions? 4) In what ways did the management of English language and the socio-political situation lead to initiate new policies that respect the Algerians' linguistic rights? 5) In what ways can a bottom-up process to language policy improve the future of English language in the educational settings and the socio-cultural practices in Algeria? To answer these questions, the research followed a mixed method research design relying on five categories of participants (two hundred university students, twenty university teachers, ten Algerian diaspora, six social media influencers, and three shop/restaurant owners) and two categories of data: quantitative data (survey to university students) and qualitative data (descriptive data from social media sources and news outlets, and interviews with all categories of participants). The collected data was analyzed using SPSS program for quantitative data and inductive thematic analysis for the interviews of qualitative data. The analysis of data resulted in: 1) Fifty-five percent of university students and the majority of other categories participants believe that the pressure the SR affected the government decisions related to English language, while 33% of university students believe that there are other factors (linguistic landscape, business, education, globalization, social media, interest in English culture) that also triggered the government decisions; 2) Seventy-one percent of Algerian students believe that the SR protests are effective in attaining linguistic rights; 3) There is a reigning acceptance of the government decisions by all participants despite the distrust in the government decisions; 4) The sociolinguistic situation in Algeria shows that there is social and political rejection towards French language that led to preference of a neutral language (English); 5) English language is perceived as international language, language of communication, language of development, language of prestige, language of modernity, and language of science; 6) The satisfaction with the government decisions despite the distrust feelings indicates that Algerians are satisfied with the undertaken bottom-up approach; 7) Considering a bottom-up approach means English would have more presence at schools and universities; 8) The post-SR practices of the government go hand in hand with the public needs, beliefs, ideologies, and practices of foreign languages. The promised short-, medium- and long-plan changes of the government (related to English language) are expected to create massive changes in language-in education policy and language policy in the future. This area is believed to be a fruitful area of research for language policy and planning researchers.

ÖZ: Bu tez çalışmasında, birden fazla dilin konuşulduğu Cezayir'de yabancı dillerin (özellikle İngilizcenin) dil politikası tartışılmaktadır. Çalışma, Spolsky’nin (2004) dil politikası teorisinin bağımsız ülkelerde test edilmesi çağrısına bir yanıt olarak düşünülebilir. Teorinin test edilmesinde dile ilişkin inançlar, uygulamalar ve dil yönetimi göz önünde bulundurulmuştur. Çalışmada şu araştırma sorularına yanıt aranmıştır: 1) Cezayirlilerin yabancı dil politikasındaki değişimi tetiklemede etkili olan ‘yabancı dillere ilişkin inançları ve ulusal ideolojileri’ nelerdir? 2) Gülümseme Devriminden sonra Cezayirlilerin İngilizce dilindeki uygulamaları nasıl farklılaşmıştır? 3) Katılımcılar, İngilizce diline ilişkin uygulamaların, Gülümseme Devrimi sonrasındaki hükümet kararları üzerindeki etkisini nasıl değerlendirmektedirler? 4) İngilizcenin yönetimi ve sosyo-politik durum, Cezayirlilerin dil haklarına saygı duyan yeni politikaların başlatılmasına nasıl yol açmıştır? 5) Dil politikasında tabandan tavana doğru ilerleyen bir süreç, Cezayir'deki eğitim ortamlarında ve sosyo-kültürel uygulamalarda İngilizce dilinin geleceğini hangi yollarla geliştirebilir? Bu soruları yanıtlamak için karma araştırma yöntemi kullanılmıştır. Veri, üniversite öğrencileri, üniversite öğretim elemanları, yurtdışında yaşayan Cezayirliler, sosyal medya etkileyicileri ve mağaza/restoran sahiplerinden oluşan beş farklı katılımcı kategorisinden toplanmıştır. Nicel veriler üniversite öğrencilerine uygulanan bir anket yoluyla toplanmış; nitel veriler ise sosyal medya kaynaklarından ve haber kuruluşlarından toplanan bilgiler ile her kategorideki katılımcı temsilcileriyle yapılan görüşmelerden elde edilmiştir. Toplanan nicel veriler SPSS programı ile, nitel veriler ise tümevarımsal tematik analiz yöntemi kullanılarak analiz edilmiştir. Elde edilen bulgular şöyle özetlenebilir: 1) Üniversite öğrencilerinin %55'i ve diğer kategorilerdeki katılımcıların çoğu, Gülümseme Devriminin baskısının hükümetin İngilizce diliyle ilgili kararlarını etkilediğine inanırken, üniversite öğrencilerinin %33'ü hükümet kararlarını tetikleyen 'dilbilimsel alan, iş dünyası, eğitim, küreselleşme, sosyal medya, İngiliz kültürüne ilgi’ gibi başka faktörlerin varlığına dikkat çekmiştir; 2) Cezayirli öğrencilerin %71'i Gülümseme Devrimi protestolarının dil haklarının elde edilmesinde etkili olduğuna inanmaktadır; 3) Bulgular, hükümet kararlarının tüm katılımcılar tarafından kabul edildiğini göstermesine karşın, halk ve politikacılar arasında bir boşluk olduğunun kanıtı olarak hükümet kararlarına duyulan güvensizliği de işaret etmiştir; 4) Cezayir'deki toplumdilbilimsel durum, Fransızca’ya karşı tarafsız bir dilin (İngilizcenin) tercih edilmesine yol açan sosyal ve politik bir reddedişin olduğunu göstermektedir; 5) İngilizce dili, katılımcılar tarafından uluslararası dil, iletişim dili, gelişme dili, prestij dili, modernite dili ve bilim dili olarak algılanmaktadır; 6) Çalışmaya katılan Cezayirliler güvensizlik duygularına rağmen hükümetin dile ilişkin kararlarından memnuniyet duyduklarını ifade etmişlerdir. 7) İngilizcenin gelecekte okullarda ve üniversitelerde daha fazla yer alacağı öngörülmüştür; 8) Devletin Gülümseme Devrimi sonrasındaki uygulamaları, toplumun yabancı dil gereksinimleri, inançları, ideolojileri ve uygulamaları ile el ele gitmektedir. Hükümetin İngilizce diline ilişkin vaadettiği kısa, orta ve uzun vadeli değişikliklerin, gelecekte eğitim alanındaki dil politikasında büyük değişiklikler yaratması beklenmektedir. Bu nedenle söz konusu alan, dil politikası ve planlaması alanında çalışan araştırmacılar için verimli bir araştırma alanı olma özelliğini korumaktadır.
Doctor of Philosophy in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2022. Supervisor: Prof. Dr. Ülker Vancı Osam
Keywords: English Language Teaching (ELT) Department; Language--Foreign Languages--English--Language Policy--Algeria; English language--Study and teaching--Algeria; Smile revolution, language policy, English language, foreign language policy, language beliefs, language practice, language management, bottom-up approach